KOPERASI KAMILA BERKAH DALAM PEMBERDAYAAN PEREMPUAN - Ariesta .; Sri Rahmadani; Wibi Wijaya (Turast: Jurnal Penelitian dan Pengabdian, 2021)
This article describes a Microfinance Institution that grows and develops in the community called the Kamila Berkah cooperative which was established in Nagari Ampang Kuranji, Dharmasraya Regency, West Sumatra. This cooperative is fostered by the Sociology study program of STKIP PGRI West Sumatra with the aim of empowering the community, especially women, as an answer to women's difficulties in accessing sources of capital in opening businesses and being economically independent, so that women can get out of poverty and the consequences of poverty. women will accept. The strategies implemented in empowering women through this cooperative are through mentoring activities, thematic discussions, supervision and capacity building of cooperative members.